ANALISIS PENGARUH ATRIBUT PRODUK DAN PSIKOLOGI KONSUMEN TERHADAP BRAND SWITCHING SERTA VARIETY SEEKING SEBAGAI VARIABEL MODERASINYA (STUDI PADA KONSUMEN KOPI KAPAL API INSTAN DI KOTA PEKANBARU) - Dita Agustri Wulan; Alvi Furwanti Alwie; T. Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to find out how the influence of product attribute variables, consumer psychology of brand switching and variety seeking as simultaneous moderation variables on the consumers of Instant Kapal Api in Pekanbaru city. As for the population of this study are 12 districts in the city of Pekanbaru with 120 people ever make a switch shift from Kapal Apito other coffee brands as well as a respondent in each district obtained 10 respondents. The analysis used is descriptive analysis. Besides, it uses quantitative analysis with path analysis and assisted by SPSS program version 21. From the results of tests that have been done indicate that the relationship. 1. Product attributes have a significant effect on variety seeking. 2. Consumer psychology has a significant effect on variety seeking. 3. Variety seeking has significant effect on brand switching. 4. Product attribute significantly influence brand switching. 5. Consumer psychology has a significant effect on brand switching. 6. Product attributes, consumer psychology combined significantly effect on variety seeking. 7. Consumer product and psychology attributes, and combined combined variety seeking have significant value influencing brand switching.Keywords : Product Attributes, Consumer Psychology, Variety Seeking, Brand Switching`